2007
DOI: 10.1007/s00464-007-9546-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic fundoplication: Nissen versus Toupet two-year outcome of a prospective randomized study of 200 patients regarding preoperative esophageal motility

Abstract: Tailoring antireflux surgery according to the esophageal motility is not indicated, as motility disorders are not correlated with postoperative dysphagia. The Toupet procedure is the better operation as it has a lower rate of dysphagia and is as good as the Nissen fundoplication in controlling reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
141
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(166 citation statements)
references
References 46 publications
12
141
0
13
Order By: Relevance
“…It has been suggested that manometry could subgroup gastroesophageal reflux disease patients into those requiring partial or total fundoplication treatment [29][30][31] . However, studies have not been able to prove that preoperative manometry could predict postoperative outcome in terms of dysphagia [32][33][34] . Measurement of axial force is more likely to identify patients who would develop postoperative dysphagia, although proof awaits clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that manometry could subgroup gastroesophageal reflux disease patients into those requiring partial or total fundoplication treatment [29][30][31] . However, studies have not been able to prove that preoperative manometry could predict postoperative outcome in terms of dysphagia [32][33][34] . Measurement of axial force is more likely to identify patients who would develop postoperative dysphagia, although proof awaits clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Cerrahi tamir hedefleri semptomları geçir-mek, cerrahi işlemle ilgili morbidite ve mortaliteyi düşürmek, bakım maliyetini azaltmak ve tekrarlama olasılığını azaltmaktır. Ancak uygulanacak cerrahi tedavinin şekli konusunda tartışmalar olmaktadır (13)(14)(15)(16). Torakotomiyi daha morbit bulup batından yaklaşımı tercih edenler olduğu gibi, periözofajit gibi ortaya çıkabilecek iltihabi sorunlardan ötürü yoğun plevral yapışıklıklara hakim olabilmek için torakstan yaklaşımı uygun bulanlar da vardır.…”
Section: Cerrahi Tekniklerunclassified
“…Bu işlemde başarı oranı %85-95 civarlarındadır (13)(14)(15). Antireflü işlemlerin güvenilirliği ve komplikasyon oranları değişkenlik göstermektedir (15,16). Belsey Mark IV'ün başarı oranı %85'lerdedir (10,16).…”
Section: Cerrahi Tekniklerunclassified
See 1 more Smart Citation
“…[23][24][25][26] Multiple adult studies have shown that patients who have abnormal pHmetry and pHMII findings preoperatively are most likely to benefit most from fundoplication. [27][28][29] This experience have not easily translated to the pediatric setting, where pH-metry and pHMII based symptom association is harder to apply. In children, Rosen et al used pHMII to predict fundoplication outcome.…”
mentioning
confidence: 99%